2021
DOI: 10.3390/diagnostics11020182
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Impact on Diagnostic Innovations: Emerging Trends and Implications

Abstract: Diagnostic testing remains the backbone of the coronavirus disease 2019 (COVID-19) response, supporting containment efforts to mitigate the outbreak. The severity of this crisis and increasing capacity issues associated with polymerase chain reaction (PCR)-based testing, accelerated the development of diagnostic solutions to meet demands for mass testing. The National Institute for Health Research (NIHR) Innovation Observatory is the national horizon scanning organization in England. Since March, the Innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…Along with the ongoing vaccination efforts, easy and cheap detection systems are urgently needed to control disease spread, especially to control the unexpectedly rapid spread of escaped mutant viruses [ 237 ]. Antigen and Ab detection tests are promising candidates to fill this need and are widely used in many countries, giving the products an enormous market value [ 238 ]. The use of these products can represent a major clinical cost-saving practice, due to their low pricing, convenient and timely detection of infectious diseases with limited or no symptoms, acceleration of decisions regarding treatment or isolation, and reduction of other complications [ 239 ].…”
Section: Perspectivementioning
confidence: 99%
“…Along with the ongoing vaccination efforts, easy and cheap detection systems are urgently needed to control disease spread, especially to control the unexpectedly rapid spread of escaped mutant viruses [ 237 ]. Antigen and Ab detection tests are promising candidates to fill this need and are widely used in many countries, giving the products an enormous market value [ 238 ]. The use of these products can represent a major clinical cost-saving practice, due to their low pricing, convenient and timely detection of infectious diseases with limited or no symptoms, acceleration of decisions regarding treatment or isolation, and reduction of other complications [ 239 ].…”
Section: Perspectivementioning
confidence: 99%
“…Hence, there are many developments underway to gather data about individuals for better handling of this pandemic [42]. Due to the industrial development, wearable sensor and related technologies are effectively contributing in symptoms reporting and managing the disease [43,44]. Furthermore, the latest technologies such as deep learning (DL) has also been effectively applied on the user's generated/reported data for the diagnosis of COVID-19 in recent times [45].…”
Section: Symptoms and Other Data Reporting To Health Authoritiesmentioning
confidence: 99%
“…Lateral flow assays are commonly used for rapid clinical testing, such as COVID-19 serological tests, antigen tests, certain molecular tests, and the neutralizing antibody test [ 29 , 30 , 31 , 32 , 33 ]. Wang et al reported on the use of a lateral flow dipstick assay with wild-type and the South African spike S1 protein for the characterization of the neutralizing activity of post-vaccination plasma samples [ 29 ].…”
Section: Discussionmentioning
confidence: 99%